Eksploitasi Pesisir Pantai Bali Utara Sebagai Sumber Inspirasi Seni Instalasi - Made Bayu Ariada; I Nyoman Rediasa; Langen Bronto Sutrisno (Universitas Pendidikan Ganesha, 2026)
The creation of this installation artwork aims to convey damage observed in environmental issues, with coastal areas that are beginning to be exploited now represented in the installation artwork to invite people to reflect on the damage to coastal areas. Exploitation is one of the activities carried out arbitrarily to utilize natural resources. Coastal exploitation is used as a source of visual ideas for the creation of artwork using a practice-based research (PBR) method. The research stages include site observation, documentation, concept design, and development of the work by visual arts experts. Techniques in creating installation art works using environmentally friendly materials to be able to imitate or mimic forms and places according to the exploited environmental conditions, art works that do not emphasize aesthetics but rather the reality of coastal environmental damage that has been encountered, so that they can be used as references or sources of inspiration in the development of contemporary visual art. Keywords: Bali Beach, Exploitation, Visual Inspiration, Practice-Based Research, Installation Art